MRI of subcutaneous granuloma annulare: A series of four cases: Magnetna resonanca podkožnega granuloma anulare: serija štirih primerov - Jug, Liona; Rupreht, Mitja (Acta Medico-Biotechnica, 2023)
Background: Subcutaneous granuloma annulare (SGA) is a rare benign soft tissue mass that occurs mostly in the lower limbs of young children. Detailed knowledge of imaging findings is needed to avoid unnecessary invasive diagnostic procedures.Materials and Methods: One follow-up case and three companion cases are presented. All children were between the ages of 5 and 10 years.Results: The MRI findings demonstrated ill-defined subcutaneous masses in three cases while in one case the mass was mildly hypointense and heterogeneous on fluid-sensitive sequences. Contrast agent was administered intravenously only in one case, where moderate enhancement was observed.Conclusion: Detailed clinical description of the lesion location was crucial. In addition, knowledge of MR imaging findings was necessary for a correct diagnosis to reassure the parents and avoid unnecessary invasive diagnostic procedures.
Keywords: subcutaneous granuloma annulare, soft tissue tumor, children, magnetic resonance, MRI